Analisis Financial Value Added (FVA) sebagai metode pengukuran kinerja keuangan perusahaan dalam upaya mencapai sustainable competitive advantage - Indra, Nurhayat; Nurulia, Nisa; Dewi, Lely Savitri (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Measurement of a company's financial performance is often done using financial ratios that are analyzed from the company's financial statements for a certain period. Performance measurement based on financial ratios has not been able to reflect the company's overall performance. Therefore, a financial performance measurement tool is needed that shows the actual performance of management with the aim of encouraging activities and strategies that add economic value and discarding activities that do not add value. Financial Value Added (FVA) is part of the concept of evaluating the performance of company management by generating added value created by the company during the research period. This study aims to determine the financial performance of companies in the cosmetics and household goods sub-sector using the FVA method and to determine its relationship to sustainable competitive advantage during the study period, also using Return on Assets (ROA) and Operating Ratio (OR). The results showed that FVA, ROA, and OR in the cosmetics and household goods sub-sector companies showed that they had sustainable competitiveness in the market except for PT. Martina Berto Tbk and PT. Mustika Ratu Tbk, which still have low competitiveness in the industry.